14-3(n)=26

Simple and best practice solution for 14-3(n)=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14-3(n)=26 equation:



14-3(n)=26
We move all terms to the left:
14-3(n)-(26)=0
We add all the numbers together, and all the variables
-3n-12=0
We move all terms containing n to the left, all other terms to the right
-3n=12
n=12/-3
n=-4

See similar equations:

| -c+7/2=2 | | 9.67-3.6g=-4.4g+3.99 | | 19-4p=5 | | -9(z+2)=63 | | Y^2-26y+169=-13 | | -112=-6(2v+2)-4 | | 9.67-3.6g=4.4g+3.99 | | 3(x-7)=4x+8 | | K(-c)=|-c-2| | | p(p-2)=15 | | 6(-5+4n)-8=-206 | | 48=8(y-4) | | 450-40x=975-67x | | (5x-3)(4x+9)=0 | | -30=26-8.9x | | 756/(401-x)=6 | | 1+7(-3a+5)=183 | | 15=-3(2x+1) | | 4c+9=c | | 10-6m=-9-9m-2 | | 3(x-7)=4x-8 | | -95=-4-7(x+5) | | 30=10c-5c | | n^2−5n−2=0 | | -2.6b+4=0.9b–17. | | -4-9p=2-10p | | 7x(x-5)=-12 | | u+6/6=3 | | 85=1.8x-80 | | -10+5p=6-6+3p | | 4t^2+11t+2=4t | | -2z+8z=-24 |

Equations solver categories